Regional ultimate tensile strength and water sorption/solubility of bulk-fill and conventional resin composites: The effect of long-term water storage - Rummani, Ghassan; Ide, Kurumi; Hosaka, Keiichi; Tichy, Antonin; Abdou, Ahmed; Otsuki, Masayuki; Nakajima, Masatoshi (Dental materials journal, 2021)
The effect of long-term water storage on the regional ultimate tensile strength (UTS), water sorption (Wsp) and water solubility (Wsl) of conventional and bulk-fill resin composites at various depths was investigated. Composite specimens light-cured from one side were sectioned into beams corresponding to different depths (1-5 mm) and stored in water for 24 h, 1 week, 1 month, 6 months or 1 year. UTS increased during the first week and then gradually decreased over time, especially in deeper regions. Bulk-fill composites initially exhibited similar UTS at all depths, whereas the UTS of conventional composites at 1 mm and 5 mm differed significantly at all time points. Wsp and Wsl increased with depth and storage time, markedly at 3-5 mm after 1 month for conventional composites and after 6 months for bulk-fill composites. The signs of degradation at depths beyond 3 mm suggested that even bulk-fill composites have suboptimal properties in layers more than 3 mm in thickness.
Keywords: Solubility; voda; Water; rozpustnost; testování materiálů; polymerizace; složené pryskyřice; Materials Testing; Composite Resins; pevnost v tahu; Tensile Strength; Polymerization